Thermal Stresses in an Orthotropic Elastic Slab Due to Prescribed Surface Temperatures - T. R., Tauchert; A. Y., Aköz (ASME International, 1974)
The stresses in an orthotropic, elastic slab resulting from a stationary, two-dimensional temperature field are examined. A general method of solution based upon displacement potentials is presented for the case of prescribed surface temperatures. Both the plane-strain and plane-stress problems are discussed. As an illustrative example, the stresses resulting from a uniform temperature rise over a portion of one face of the slab are computed; numerical results are given for a fiber-reinforced composite material.
Keywords: Thermal effects in solid mechanics; Anisotropy in solid mechanics; Thin bodies, structures